1994
DOI: 10.2307/1939386
|View full text |Cite
|
Sign up to set email alerts
|

Acorn Production by Oaks in Central Coastal California: Variation within and among Years

Abstract: We measured acorn production by individual oaks of five different species at Hastings Reservation in central coastal California between 1980 and 1991. Variation in acorn production was considerable both within and among years and was generally uncorrelated between species. Compared to expected values, variance within years in the size of acorn crops was small, while variance among years was high. Crop failures occurred fairly frequently and large crops in successive years were observed, but not more than expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
256
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(270 citation statements)
references
References 18 publications
13
256
0
1
Order By: Relevance
“…The temporal pattern of seedling recruitment shows large between-year variability ( figure 3). This variability is consistent with the pattern of high and low acorn production found by Siscart et al [28] for holm oak in a nearby area during these years, and has also been observed in other Quercus species [8,17,18,29]. In fact, the lack of seedling recruitment found in this study in 1994 agrees with the very low acorn production found in 1994 by Siscart et al [28], and could be related to the extreme drought of that year.…”
Section: Discussionsupporting
confidence: 92%
“…The temporal pattern of seedling recruitment shows large between-year variability ( figure 3). This variability is consistent with the pattern of high and low acorn production found by Siscart et al [28] for holm oak in a nearby area during these years, and has also been observed in other Quercus species [8,17,18,29]. In fact, the lack of seedling recruitment found in this study in 1994 agrees with the very low acorn production found in 1994 by Siscart et al [28], and could be related to the extreme drought of that year.…”
Section: Discussionsupporting
confidence: 92%
“…Although several theories have been advanced to explain the evolution of such masting behaviour, there is currently no consensus on its ultimate cause (Kelly 1994;Koenig et al 1994). Research has shown, however, that during years of high seed production, most, if not all, mature trees within the population reproduce (Silvertown 1980;Sork et al 1993), creating an overall consistent spatial pattern of seed rain abundance between such years.…”
Section: Discussionmentioning
confidence: 99%
“…The second explanation assumes that rowan trees have a large fruit crop when they accumulate a sufficient amount of resources. It has often been asserted that mast species must store resources in more than 1 year to produce large crops (Sork et al 1993;Koenig et al 1994;Satake and Iwasa 2000). If the conditions favoring tree ring growth are also good for resource storage, trees with a higher growth increment will have more reserves and yield a bigger fruit crop the next year.…”
Section: Radial Growth Increment (Mean) (Mm)mentioning
confidence: 99%